2009
DOI: 10.1097/sap.0b013e3181877afa
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Enalapril on Skin Flap Viability is Independent of Angiotensin II AT1 Receptors

Abstract: Random pattern skin flaps are still widely used in plastic surgery. However, necrosis in the distal portion resulting from ischemia is a serious problem, increasing the cost of treatment and hospitalization. To enhance skin flap viability, a variety of pharmacologic agents have been intensively investigated. The aim of this study was to assess the effect of enalapril (an angiotensin-converting enzyme inhibitor) and losartan (an angiotensin receptor blocker) in skin flap viability. Male rats of 200 to 250 g wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 51 publications
1
8
0
Order By: Relevance
“…Wray et al demonstrated that isoxsuprine, propranolol, and heparin increased flap survival in a porcine flap model that had a proximal axial portion and a distal random portion (McFarlane, Deyoung, & Henry, ). Pazoki‐Toroudi, Ajami, Habibey, Hajiaboli, and Firooz () reported that enalapril (an ACEI) increased flap survival in a random pattern skin flap rat model, while losartan (an ARB) decreased flap survival. Rinker et al assessed the effect of verapamil (a CCB) on smoking‐induced skin flap necrosis in McFarlane‐type caudally‐based skin flaps and found that treatment with the CCB was associated with a statistically significant improvement in flap survival (Rinker, Fink, Barry, Fife, & Milan, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Wray et al demonstrated that isoxsuprine, propranolol, and heparin increased flap survival in a porcine flap model that had a proximal axial portion and a distal random portion (McFarlane, Deyoung, & Henry, ). Pazoki‐Toroudi, Ajami, Habibey, Hajiaboli, and Firooz () reported that enalapril (an ACEI) increased flap survival in a random pattern skin flap rat model, while losartan (an ARB) decreased flap survival. Rinker et al assessed the effect of verapamil (a CCB) on smoking‐induced skin flap necrosis in McFarlane‐type caudally‐based skin flaps and found that treatment with the CCB was associated with a statistically significant improvement in flap survival (Rinker, Fink, Barry, Fife, & Milan, ).…”
Section: Discussionmentioning
confidence: 99%
“…We evaluated flap survival area on postoperative day 7 as in previous studies on random pattern skin flap model (Pazoki‐Toroudi et al, ; Ozturk, Tezel, & Yalcin, ). But, most flaps were not fully demarcated on postoperative day 7.…”
Section: Discussionmentioning
confidence: 99%
“…Regardless of their great potentials, skin flap applications are often limited due to the inadequate blood supply that leads to the partial or complete necrosis at distal parts of the flap (2). Ischemic damage to the flap tissue and subsequent necrosis can be augmented by clinical and pharmacological interventions that suppress oxidative tissue damage or increase tissue tolerance against injury (3,4). There are several chains of molecular and cellular events which cause flap necrosis including the lack of the nutrients and ATP, oxidative stress, and inflammatory responses (5).…”
Section: Introductionmentioning
confidence: 99%
“…Among various classes of antihypertensive medications, angiotensin receptor blockers (ARBs) have been reported to decrease skin flap survival (13,14) and deteriorate wound healing (15,16) in experimental studies. A previous retrospective study evaluating the effect of antihypertensive drugs on surgical complications after breast reconstruction in a single-center cohort has reported that ARB use was significantly associated with an increased risk of overall surgical complications in tissue expander reconstruction and perfusion-related complications in abdomen-based autologous reconstruction (17).…”
Section: Introductionmentioning
confidence: 99%